Advances in tissue banking, Vol. 3 (World Scientific Pub. Co., 1999)
This important book provides new information about the inter-disciplinary field of tissue banking and related clinical applications, and complements the previous two volumes. It gives comprehensive coverage of the regulatory framework of the subject, as well as production and sterilisation of tissue allografts (bone, skin and new substitutes). The use of tissue allografts in orthopaedic and replacement surgery for the treatment of burns, etc. is described